PENGEMBANGAN JAMUR TIRAM DENGAN TEKNOLOGI TEMPERATURE AND HUMIDITY CONTROL DAN OPTIMASI PADA PRODUKSI JAMUR TIRAM - Alvida Mustika Rukmi; M. Isa Irawan; Aunurohim . (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Oyster mushroom cultivation in Kampung Tinja Keputih, can be analternative to empower local communities to be more productive society. Theeconomic value of the oyster mushroom in the area around the target society,with ease and cheapness of oyster mushroom seeds, allowing it to be used asagricultural products in the target area. While the lack of knowledge formushroom cultivation in the lowlands become the forerunner of mushroomcultivation program with tools